Banking Sector Reforms and the Global Financial Crisis in Transition Economies: Evidence from Southeast Europe (International Journal of Scientific Research and Management (IJSRM), 2022)
In this paper we provide an overview of banking sector reforms in the transition economies of eight Southeast European (SEE) countries. We discuss certain macroeconomic and financial sector indicators of SEE countries leading up to the Global Financial Crisis and immediately after. We benchmark these indicators with Central Eastern European and EU 15 countries in order to identify financial development gaps and areas for improvement. This paper is intended to contribute to the discussion on the economic convergence of EU and new or potential EU member states and the degree to which reforms have contributed to a sound financial sector which will in turn fund a sustainable growth and ensure a successful EU integration.